Analysis of Empty Containers Supplies in the Shipping Network: Case Study at National Shipping Company - Heri Cahyono; I Nyoman Pujawan (Institut Teknologi Sepuluh Nopember, 2019)
National Shipping Company (NSC) is a national shipping lines servicing domestic routes and a logistic key player of sea transport in Indonesia. Focus of this research is to determine total containers inventory for all routes, containers safety stocks at primary ports as well as optimum empty containers reposition strategy based on market’s requirement, all with purpose to avoid potential empty containers shortage. Unbalanced container turnover between inbound and outbound is a global issue in the shipping industry. A very common method applied by shipping operators in balancing supply and demand is repositioning excess containers to deficit areas. Determination of total container inventory begins with the calculation of safety stock of container inventory in Surabaya and Jakarta as a demand location port. Main parameter forming the calculation model is forecast cargo at home base port per route, service schedule as well as swiftness of cargo stuffing and stripping. Furthermore, determining the best routes combination shall reduce amount of container inventory. Calculation model of producing total container inventory which should be provided in 2018 is 46,382 TEUs while total existing NSC’s inventory in 2018 is 48,567 TEUs. From the total existing inventory, 2,516 TEUs turned out to be inactive (idle) for more than 30 days, meaning the active ones were 46,051 TEUs. From this comparison, calculation model is able to describe existing condition at 99.3%. Using the same model, a change in route combination with a pendulum nusantara service was carried out, which resulted in 968 TEUs reduction of container potential and reduction of one vessel allocation. This leads to potential efficiency of IDR 40,624,648,190 (forty billion six hundred twenty four million six hundred forty eight thousand one hundred and ninety Rupiah) for operational of year 2018